Rimigs: the impact of gamification on students’ motivation and performance in programming class - Ferdian Aditya Pratama; Riana Magdalena Silitonga; Yung-Tsan Jou (Institute of Advanced Engineering and Science, 2021)
Gamification is described as the art of changing human activity to a game-like environment to gain user engagement. Rimigs is a developed gamification system discussed in this research and was built based on Octalysis framework. This research aims to design and identify the impact of using a gamification system on students’ motivation and performance, especially in programming classes. Through Rimigs, students’ engagement and performance can be enhanced by freely choosing tasks or quests according to the rank points, completing these tasks or quests, getting experience points, getting rewards, avoiding punishment at certain times, and competing with others friends. The proposed research was done by using the iterative methodologies and consists of four phases, starting from i) literature review, which identifies the Octalysis’ core, ii) design, which identifies the game elements used in the system and designing the unified modeling language (UML) diagram of the system, iii) testing, which involve the user in the using of the system, and iv) implementation, which is the analysis step for the impact of Rimigs in students’ performance and engagement. This research finds that Rimigs as a gamification system can positively impact both students’ motivation and performance.